THE EFFECT OF WORKLOAD AND WORK ENVIRONMENT ON JOB SATISFACTION IN COMPANY EMPLOYEES - Amalia Rachmawati Nur Fadhilah; Wawan Prahiawan (LPPM Universitas Banten jaya, 2024)
The purpose of this study is to find out more about the relationship between workload, work environment and employee job satisfaction in the company. Researchers conduct qualitative research with the aim of gaining an in-depth understanding of reality using an inductive approach. Data analysis is carried out using the descriptive analysis method, which involves describing existing facts and analyzing them. The results show that a working environment that provides support and recognition of employee achievements has an important role in reducing the negative impact of excessive workload, increasing employee satisfaction and well-being. An improved work environment also contributes to employee satisfaction, increasing productivity and employee loyalty. This can be an effective tool for companies to achieve their business goals more efficiently and effectively.